Examining trends in ICT statistics: How does the Philippines fare in ICT? - Jose Ramon G. Albert; Ramonette B. Serafica; Beverly T. Lumbera (Philippine Institute for Development Studies (PIDS), 2016)
In the past one and a half decades, the world has vastly changed economic transactions, data sharing, and the entire general way of life given the dynamic and innovative landscape brought about by information and communications technologies (ICT). This paper first describes the deluge of digital data known as Big Data and its potentials for generating socioeconomic statistics given issues of veracity and privacy. It also gives a brief history of the Internet in the Philippines and discusses the increased Internet access and usage in the country. Other ICT statistics that describe a host of issues regarding the ICT sector, particularly infrastructure and the policy environment, are also examined. Finally, the paper provides some suggestions on how the country can make its digital dividends more inclusive.
Keywords: 330; ICT; Big Data; internet; social media; veracity; privacy; digital dividends